Effect of the Wii Sports Resort on Mobility and Health-Related Quality of Life in Moderate Stroke - Iratxe Unibaso-Markaida; Ioseba Iraurgi (Behavioural Neurology)
Background. Stroke is a common cerebral circulatory disorder that has several sequelae that affect the daily life of patients as well as their quality of life and the lives of people close to them. Video games are being used in the rehabilitation process to address these sequelae and their benefits are shown on physical activity and in the cognition area. However, their effects on daily life activities and quality of life are not known. This study was aimed to test the effect of the Nintendo Wii Sports Resort on mobility and health-related quality of life among patients who have suffered a moderate stroke. Methods. A prepost design study was conducted with 30 moderately impaired stroke patients aged 65±15. The study lasted eight weeks. 15 participated in the intervention group and the others belong to the control group. They were assessed in mobility (Timed Get Up and Go Test—TUG) and health-related quality of life (SF-36 Health Questionnaire). Parametric test and effect sizes were used to analyze the change in outcomes and to compare groups. Results. There were no differences at baseline between the groups. After the intervention, the intervention group had experienced a greater change according to the size of the effect on the variables concerning TUG (d=1.32), physical function (d=1.32), social function (d=0.71), and Physical Component Summary (d=0.75). On the other hand, the control group had a significant change in mental health according to effect size; however, this effect is not statistically relevant (d=0.88; CI 95%=−3.74 to 5.50). Conclusions. The results on mobility and health-related quality of life indicate an improvement in both groups. However, according to the effect sizes and its confidence of interval, the intervention group achieved better results than the control group. Although more studies are needed in this area, the results are encouraging for improving mobility and health-related quality of life after stroke.